Will you purchase what I recommend? The role of interaction orientation, parasocial relation, and product involvement - Febrianti, Adjeng Mariana; Hermina, Nurul; Suratman, Maman (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
In recent years, sales in online platforms have received huge attention from generation Z in Indonesia, along with live streaming business model which has undergone rapid development in recent years. Although the way live streaming with consumers has been known as the key to influence consumer behavior, only a few research has studied the style of streaming communication in affecting purchase intentions. Based on the social influence theory, this study attempts to examine the influence of interaction orientation, parasocial relation, and digital influencer credibility on purchase intention. In addition, the present study also investigates the role of product involvement advertised by streamers as moderator. The quantitative approach with the survey is used through samples of 200 respondents selected by purposive sampling. The data is collected online through disseminating questionnaires using Google Form, which is then analyzed using SEM-PLS technique. The findings indicate that interaction orientation positively influences purchase intention and parasocial relation, while parasocial relation positively influences digital influencer credibility, and digital influencer credibility positively influences purchase intention. In addition, product involvement has a moderating role that can strengthen the influence of interaction orientation and purchase intention. This study provides implications for how an interaction can be delivered online and how the involvement of a credible influencer can affect purchase intention.